A Rare Case of Shared Delusion of Pregnancy in a Couple Undergoing Fertility Treatment (Nepalese Medical Journal, 2022)
Pseudocyesis or phantom pregnancy is a false belief of being pregnant that is associated with objective signs and reported symptoms of pregnancy, which may include abdominal enlargement, reduced menstrual flow, amenorrhea, subjective sensation of fetal movement, nausea, breast engorgement and secretions, and labor. Though it is a very rare condition, it is often seen in women undergoing fertility treatment in developing countries. Isolated pseudocyesis in women and sometimes men have been reported before, but there are very few reports of shared delusions of pregnancy by a couple. No such report has ever been made before from Nepal. Therefore, this case report seeks to associate psychiatric/psychological, gynecological, and neuroendocrine mechanisms leading to the emergence of shared delusion of pregnancy (folie à deux) in a Nepali couple undergoing artificial reproductive techniques for the management of infertility. In this case, the couple firmly believed in their pregnancy against all medical evidence.